1981
DOI: 10.1128/jb.145.1.233-247.1981
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the functions of hemolytic plasmid pHly152 of Escherichia coli

Abstract: fined Inc characters used in this study for characterization of the incompatibility of hemolytic plasmids were obtained from Y. A. Chabbert, Paris, France. Media, chemicals, and enzymes. Usually cultures were grown in enriched nutrient broth or in alkaline broth extract. Radiochemicals were purchased from New England Nuclear Corp., Boston, Mass.; the antibiotics used were a gift from Bayer, Leverkusen, Germany. AU other chemicals were obtained from E. Merck AG, Darmstadt, Germany. Restriction enzymes were purc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

1984
1984
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 21 publications
5
74
1
Order By: Relevance
“…ShlA was obtained from the culture supernatant of IPTGinduced E. coli BL21(pRO3 shlA shlB ) by precipitation with 50% ammonium sulphate. ShlA was purified as described ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 853-865 Noegel et al (1981) above for ShlA* on a MonoS HR5/5 column (single chromatographic step). ShlA-255 was obtained by precipitation with 50% ammonium sulphate (final concentration) from the culture supernatant of IPTG-induced E. coli BL21 (pRO2 shlA shlB ).…”
Section: Haemolysis After Complementation With Pementioning
confidence: 99%
“…ShlA was obtained from the culture supernatant of IPTGinduced E. coli BL21(pRO3 shlA shlB ) by precipitation with 50% ammonium sulphate. ShlA was purified as described ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 853-865 Noegel et al (1981) above for ShlA* on a MonoS HR5/5 column (single chromatographic step). ShlA-255 was obtained by precipitation with 50% ammonium sulphate (final concentration) from the culture supernatant of IPTG-induced E. coli BL21 (pRO2 shlA shlB ).…”
Section: Haemolysis After Complementation With Pementioning
confidence: 99%
“…The hemolytic activity of E. coli strains was analyzed by cultivation of the strains on human blood agar plates as described previously [16]. S-¢mbrial adhesin expression was analyzed by a hemagglutination assay with plate-grown bacteria.…”
Section: Characterization Of Strainsmentioning
confidence: 99%
“…Bacteria were grown at 30°C in L-broth medium or on blood-agar plates containing the appropriate antibiotics at 50 ~g/ml. Plasmids pAC50 and pAC2001 are pACYC184 bearing the E. coli hly determinant from the wild-type plasmid pHly152 [11] and the chromosomal determinant LE2001 [10], respectively.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…1 E. coli 5K and mutant strain Hsb. 1 were transformed with plasmids pAC50 and pAC2001 to determine production of hemolysin when carrying the complete plasmid [11] or chromosomalderived [10] hly determinants. Extracellular hemolytic activity was measured in culture supernatants and showed that the extracellular hemolytic activity of strain Hsb.…”
Section: Reduction-of Hemolysin Synthesis and Secretionmentioning
confidence: 99%
See 1 more Smart Citation